The Cash Flow Concept in Modern Financial Analysis of Internal Sources of Companies’ Investment Financing - Rajko M. Bukvic; Radica Z. Pavlovic (Current Aspects in Business, Economics and Finance Vol. 7, 2023)
In recent theories of financial analysis, a financial approach has been adopted which is based on the dynamic (modern) coefficients established from cash flows - cash flow indicators. Some of the areas of their application are capital investments, which largely depend on internal sources of financing and the ability of companies to generate such sources of financing, especially in conditions of crisis and insolvency. In this regard, they have special importance for the Republic of Serbia, whose macroeconomic environment is further damaged by the current global world and energy crisis, insolvency, collapse and shutdown of domestic capacities, and the concentration of capital in the financial sector. In this study, the focus is on researching the difference between investment capacities based on internal sources of financing established on static and dynamic indicators, in order to prove the necessity of applying dynamic coefficients based on cash flow analysis, which are not very common in practice in Serbia. The advantages of using the mentioned parameters based on the cash flow concept as a modern tool in the research question on the example of energy as one of the most important branches of the Serbian economy were examined and proven.